Педагогічна діяльність одеського скульптора Бориса Едуардса - Кудлач, В. (Краєзнавство, 2019)
У статті висвітлюється викладацька діяльність одеського скульптора Б.В. Едуардса. Boris Vasylyovych (Vilyamovych) Edwards (1860-1924) is a multifaceted person: a first-class sculptor, a public
figure, an entrepreneur. However, the «artist-sculptor» Edwards leaves in the shade another his hypostasis – Edwards-
teacher.